The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-09596-3
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting disability-adjusted life years for chronic diseases: reference and alternative scenarios of salt intake for 2017–2040 in Japan

Abstract: Background In Japan, a high-sodium diet is the most important dietary risk factor and is known to cause a range of health problems. This study aimed to forecast Japan’s disability-adjusted life year (DALYs) for chronic diseases that would be associated with high-sodium diet in different future scenarios of salt intake. We modelled DALY forecast and alternative future scenarios of salt intake for cardiovascular diseases (CVDs), chronic kidney diseases (CKDs), and stomach cancer (SC) from 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…We followed the methodological approach of Nomura and Yoneoka et al [ 14 ]. GBD data from 1990 to 2016 were used to predict the future values from 2017 to 2040 for DALYs attributable to three disease groups that have been identified to be associated with low vegetable intake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the methodological approach of Nomura and Yoneoka et al [ 14 ]. GBD data from 1990 to 2016 were used to predict the future values from 2017 to 2040 for DALYs attributable to three disease groups that have been identified to be associated with low vegetable intake.…”
Section: Methodsmentioning
confidence: 99%
“…We used consecutive nationwide data from NHNS to characterise sex- and age-specific average daily vegetable intake and prevalence of current smoker, current alcohol drinker, and obesity (defined according to the Japanese definition of a body mass index (BMI) of 25 kg/m 2 or over) following the design of a previous study [ 14 ]. The individual data from NHNS were categorised according to the GBD’s category and combined with DALYs rate by age, sex and survey year.…”
Section: Methodsmentioning
confidence: 99%
“…Overall forecasting model structure We followed the methodological approach of Nomura and Yoneoka et al (2020) (14). GBD data from 1990 to 2016 were used to predict the future values from 2017 to 2040 for DALYs attributable to three disease groups that have been identified to be associated with low vegetable intake.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, we found that the percentage of people who meet the dietary goal for seven essential nutrients-designed to reduce the risk of lifestyle-related chronic diseases in Japan's 2015 national nutrient-based dietary guideline-was only 0.3% in 2017 [8]. We have also identified remarkable differences in disease burden between the scenarios, representing a wide scope of future trajectories of food intake with the potential for a tremendous decrease in the burden by 2040 [9] [10]. While it is important to note that foods are more than just a collection of nutrients and that focusing on individual nutrients does not necessarily translate to a healthy diet [11], there is room for Japan to improve its diet to maintain and further develop its population's health.…”
Section: Japanese Diet and Dietary Risksmentioning
confidence: 96%